PENGARUH KUALITAS LAYANAN DAN CITRA KLINIK TERHADAP KEPUASAN PASIEN PESERTA ASURANSI KESEHATAN SERTA DAMPAKNYA TERHADAP LOYALITAS PASIEN di KLINIK ANGELA NUGRAHA UNGARAN (Students' Journal of Accounting and Banking, 2013)
Service quality has become a dominant factor to the success of a company. Because if the customer  receives good of service quality, it will create satisfaction. Corporate image is believed to influence the purchasing decision, whereby a good image will stimulate the purchase. The goal of the company is customer satisfaction that is expected to have an impact on customer loyalty to the company. This research took sample of 125 respondents using non-probability sampling technique in patients at the Clinic Angela Nugraha Ungaran. The purpose of this study was to measure of service quality and corporate image on satisfaction and the impact on patients loyalty at the Clinic Angela Nugraha Ungaran. The test results are show there is a positive influence between the service quality to the satisfaction of patients,  positive influence between clinic image to patient satisfaction, positive influence between service quality to patient loyalty, clinic images does not influence to patient loyalty, a positive influence between patient satisfaction to patient loyalty. The results showed patient satisfaction did not mediate on service quality to patient loyalty and patient satisfaction mediates on clinic image to patient loyalty.   Keywords : service quality, clinic image, patient satisfaction and patient loyalty